2012
DOI: 10.1017/s0954102012000491
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for the microbial loop in Antarctic sea ice using microcosm simulations

Abstract: AbstractSea ice microalgae actively contribute to the pool of dissolved organic matter (DOM) available for bacterial metabolism, but this link has historically relied on bulk correlations between chlorophylla(a surrogate for algal biomass) and bacterial abundance. We incubated microbes from both the bottom (congelation layer) and surface brine region of Antarctic fast ice for nine days. Algal-derived DOM was manipulated by varying the duration of irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, PEPS could be used as a carbon source for bacteria, also facilitating grazing by heterotrophic and mixotrophic protists. Tightly coupled bacteria‐algae interactions have been reported in sea‐ice systems (Stewart & Fritsen, 2004) and the microbial loop is considered an important mechanism for recycling of organic matter in sea ice (Martin et al., 2012; Meiners and Michel, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PEPS could be used as a carbon source for bacteria, also facilitating grazing by heterotrophic and mixotrophic protists. Tightly coupled bacteria‐algae interactions have been reported in sea‐ice systems (Stewart & Fritsen, 2004) and the microbial loop is considered an important mechanism for recycling of organic matter in sea ice (Martin et al., 2012; Meiners and Michel, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both FT‐ICR MS‐derived molecular formulas and optical parameters suggest that the DOM of the SIM water samples is enriched in fresh, biolabile compounds, whereas the DOM of the post‐SIM water samples contains more refractory, humic‐like compounds. Taken together these observations suggest that heterotrophic bacteria in the surface water of the Southern Ocean preferentially consume smaller molecular weight compounds with low aromaticity characteristics under seasonal sea ice cover, causing selective accumulation of higher‐molecular‐weight compound with higher humification degrees (Barker et al., 2013; Imbeau et al., 2021; Martin et al., 2012).…”
Section: Discussionmentioning
confidence: 95%
“…The switch from lysogenic to lytic infection of bacteriophages during a spring bloom in the Western Antarctic Peninsula is a major control on bacterial populations and, through regenerated nutrients, indirectly influences primary production (Brum et al, 2016). It is unknown how warming oceans and reduced sea-ice thickness and duration could affect these interactions, ultimately impacting biogeochemical cycles (Martin et al, 2012a). For example, a study by Maat et al (2017) found that warmer temperatures shortened latent periods and increased burst size of Micromonas polaris viruses.…”
Section: How Do Microbial Interactions Affect Physiology?mentioning
confidence: 99%